Self-esteem and weight status of young adults: Findings from a pilot study - Echu Liu; Su-Hsin Chang (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Researchers have examined the association between self-esteem and obesity in past studies. However, most studies have focused on pediatric or adolescent populations. In this pilot study, we aim to explore the association of self-esteem with weight status in young adults, a group of individuals in a significant and pivotal period of their lives whose needs and challenges have received little attention in previous studies. MATERIALS AND METHODS: Exactly 127 college juniors and seniors in the Midwest participated in late 2017. For our survey, we collected the following information: body weight, height, self-esteem score from the state self-esteem scale, grade point average, risk of eating disorders, sleep quality, nutritional behavior, lifestyle (smoking, frequency of exercise, alcohol drinking, average daily time watching television, playing video games, and social media use), and demographic and socioeconomic background. We used logistic regression for our analysis. RESULTS: The logistic regression indicates that a one-point increase in the self-esteem score was negatively associated with a young adult's odds of having an unhealthy weight (being overweight or obese) by approximately 3%. Furthermore, soda drinking is a statistically significant factor associated with weight status. CONCLUSIONS: This finding suggests self-esteem is positively associated with a healthy weight in young adults. A larger-scale study should be conducted in the future to validate this relationship and better understand young adults' needs.